The literary works of Shaykh Sîdî Al-Mukhtâr Al-Kuntî (d. 1811) : a study of the concept and role of “miracles” in al-Minna fî I'tiqâd Ahl al-Sunna - Moos, Ebrahiem (Department of Historical Studies, 2015)
Includes abstract.~Includes bibliographical references (leaves 105-109).